Mesoscopic Characteristics and Performance Evaluation of Loess Treated by Different Anti-Seismic Subsidence Technologies - Wang, Ping; Xu, Shuya; Shao, Shengjun; Wang, Huijuan; Li, Xudong; Qian, Ziling (Frontiers in Earth Science, 2022)
The meso-structure of the soil has an important restriction on its engineering properties. Based on dynamic triaxial tests and SEM meso-structure test experiments, this study investigated the meso-scale structural deformation characteristics of samples treated by physical, chemical and compound improvement methods, before and after strong earthquakes of typical seismic subsidence loess. The evolution law of the soil microstructure after the improved method processing technology reveals the internal relationship between the soil microstructure and the seismic subsidence coefficient. On this basis, the seismic subsidence performance of the improved method is given under the conditions of frequent earthquakes, fortifying earthquakes and rare earthquakes. The results show that: (1) The physical improvement method has the most obvious effect on the elimination of macropores and overhead pore structures; (2) The chemical modification method can generate unique glass beads or flocculated fine structures, which can greatly enhance the strength of the soil and play the role of filling, cementing or buffering respectively in the event of a strong earthquake; (3) for several improved treatment methods, the amount of seismic subsidence increases nonlinearly with the increase of peak acceleration. (4) In the event of frequent earthquakes, in addition to the method of adding fly ash, the earthquake subsidence can be eliminated; when the fortification earthquake comes, the effect of purely physical improvement of the dynamic compaction method begins to show its shortcomings; the dynamic compaction-cement-soil composite method completely eliminates the seismic subsidence of the site. The dynamic compaction-fly ash composite modification method can ensure that the foundation is maintained at moderate damage and also show its good effects. This research has important theoretical significance and practical value. The related results can give reasonable suggestions for the treatment of seismic subsidence of different foundations in the "resilient urban and rural" and key engineering construction and seismic design of China's loess area.